A Novel SLM based PAPR reduction Technique in OFDM-MIMO System - Singh, Er. Sukhjinder; Malhotra, Er. Jagjit; Singh, Er. Manwinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Orthogonal Frequency Division Multiplexing (OFDM) is annew method for fourth generation wireless communication.MIMO-OFDM has become a promising candidate for highperformance 4G broadband wireless communications.However, one main disadvantage of MIMO-OFDM is thehigh peak-to-average power ratio (PAPR) of the transmitter’soutput signal on different antennas. In this paper, we present anew noble SLM PAPR reduction techniques such asselective mapping technique and Partial transmit sequencetechniques and shows which of these PAPR reductiontechniques are more effective to reduce PAPR in OFDMMIMO.